Information needs and information-seeking behavior of doctors at the University of the Philippines College of Medicine-Philippine General Hospital (UPCM-PGH) a user study - Tinay, Froilan P. (School of Library and Information Studies, University of the Philippines Diliman, 2003)
The explosion of medical knowledge has been so overwhelming that doctors today are experiencing an information overload. This situation gets worse day by day and will continue to do so in the foreseeable future. To cope with this problem, it is vital to study the information needs and patterns of information and library use of doctors. It is essential to the design of information systems in general and to the provision of effective information services in particular.